DETERMINAN IMPOR SERAT KAPAS DI INDONESIA TAHUN 1975-2014 (PENDEKATAN ERROR CORRECTION MECHANISM) - Nida'ul Hanifah; Fitri Kartiasih (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2018)
The activity of textile sector and textile product (TPT) in Indonesia keeps growing from year to year.TPTIndustry has become the main contributor of foreign exchange from non-oil and gas sector. Unfortunately, the domestic supply of cotton fiber, main material of textile product, can’t fulfill textile industry’s demand. It forces the nation to import the raw materials. Based on the problem about the import that still exist until the present, it is necessary to do a research to analyze the development of cotton fiber import in Indonesia and to identify the factors affecting the development of Indonesian cotton fiber imports during 1975-2014. This research uses descriptive analysis and inference analysis. The descriptive analysis method used in this research is graphical analysis, while the inference analysis is Error Correction Mechanism (ECM) method. Based on the estimation made with ECM, it was found that 5 variables significantly affect the cotton import volume in the long term, including: real per capita Gross Domectic Product (GDP), international cotton fiber prices, domestic cotton fiber production, the demand of cotton fiber by domestic yarn spinning industry and textile product exports volume. While in short term, only 4 variables significantly affect thecotton fiber import volume: domestic cotton fiber production,the demand of cotton fiber by domestic yarn spinning industry, real per capita GDP and textile product exports volume. Keywords: import, cotton fiber, Textile Industry and Textile Product (TPT),Error Correction Mechanism (ECM).